Physical and numerical modeling of clayey slopes reinforced with roots - Lozada, Catalina; Mendoza, Cristhian; Amortegui, Jose Vicente (Springer Nature, 2022)
The purpose of this study was to explore the influence of vegetation on the stability of clayey slopes. Physical models with varying layer depths reinforced with roots were performed in a geotechnical centrifuge. The soil reinforced with vegetation was simulated with a mixture of clay and fiberglass which present similar shear strength properties. Displacement vectors of the physical models are obtained using the Particle Image Velocimetry (PIV). The computed resultant displacements showed that the slip surface varied with respect the root depth. Additionally, numerical models of the tests in centrifuge were made using finite elements and Bishop’s method. The results obtained also show that the deeper the roots, the deeper the sliding surface. The slip surface moves from a depth of the slope toe (slope without reinforcement) to a depth close to twice the height of the slope. Regarding the factor of safety, it varies from a value of 0.7 for slopes without vegetation to 1.19 for a root depth of three meters. Moreover, the factor of safety increases as root depth increases.
Keywords: Roots reinforcement; Clayey soil; Slope stability; Geotechnical centrifuge